Analysis of parameters of quality of life of students of different specialities - Kurko Ya.V (Kharkov National Pedagogical University, 2012)
The basic indexes of quality of student's life are considered. In research is used data of the questionnaire questioning of students of different specialities of 1st and 2nd courses (aged 17 - 20 years). The comparative analysis of changes of parameters of quality of life is conducted. The dynamics of basic indexes of quality of students' life is set in the process of studies. Intercommunication of parameters of subjective evaluation of standard of living and factors of his forming depending on specialization of studies is educed. The negative tendencies of worsening of level of quality of life are set for the students of first and second courses.